Dph3 is involved in migration and proliferation of melanoma cells. - Sin, Yen Suan. (2010)
Malignant melanoma is a highly invasive form of skin cancers characterized by rapid metastasis and resistance to chemotherapy. The development of more effective therapeutic strategy is crucial to treatment of malignant melanoma. Preliminary study has been done to identify Dph3 gene as potential factor of melanoma metastasis by using insertional mutagenesis. Here, we show that the expression of Dph3 gene is associated with melanoma cell migration. Using over-expression and down-regulation of Dph3 gene expression, we found that Dph3 rapidly induces migration and invasion of B16F10 murine melanoma cells, but dramatically suppresses proliferation in melanoma cells. We observed up-regulation of protein expression levels which are related to the progression of melanoma cells and may contribute to the effects of Dph3. Collectively, these data indicate that Dph3 gene acts as a novel regulator of melanoma migration, invasion and proliferation, implicating that it may be an effective therapeutic target for treatment of metastatic melanoma in future.